Optimizing resistance exercise adaptations through the timing of post-exercise carbohydrate-protein supplementation - Ivy, J.; Ferguson, L. (Strength and Conditioning Journal, 2010)
Proper nutritional supplementation is critical for recovery from intense resistance exercise. recent research has demonstrated the effectiveness of carbohydrate-protein supplementation in restoring muscle glycogen, repairing muscle damage, attenuating protein degradation, and initiating protein synthesis. we describe the mechanisms by which carbohydrate-protein supplementation can speed recovery and optimize training adaptations. we also suggest ways in which a nutritional strategy can practically be put into effect by those who perform resistance exercise training.